Analisis Dampak Investasi Ibu Kota Negara (IKN) Terhadap Keuangan Negara: Studi Kasus Pembiayaan Infrastruktur - Saroyo, Bagus Anggit; Azahra, Difa Ariedhita Jahada; Fasya Afifa, Tiara (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
The relocation of the Ibu Kota Negara(IKN) from Jakarta to East Kalimantan is a strategic initiative formulated by the Indonesian government to overcome challenges for the Indonesian nation and encourage equitable development throughout Indonesia. This project aims to create a modern, inclusive and sustainable government center, as well as optimize the potential of regions outside Java. Through investment in infrastructure development, transportation, energy and public services, it is hoped that IKN can accelerate national economic growth and create new jobs. Regulations that support investment in effective risk management are key to ensuring the success of these large projects. By involving all stakeholders, it is hoped that the transfer of IKN can be a step forward in creating more equitable and just development throughout Indonesia.Keywords: ibu kota negara;invesment; sustainable development; equality; east kalimantan